Improving Student’s Motivation and Learning Result Through Use Video Based Learning at SMA Singosari Delitua - Saragih, Marice; Sihaloho, Binner; Ginting, Devita Permatasari (JCEIT: Journal of Computer Engineering and Information Technology, 2025)
The use of video based learning is the appropriate media that use for the students in  this modern era. Learning by using video open the door and it make the students  more interesting and memorable learning experience for the students.. In improving education, it is necessary to apply the use of learning media to students, so that students are more motivated to participate in learning and get maximum grades, and it become an interesting aspect in increasing of the students motivation and the effectiveness in the learning process. The objective of this research is to find out the studentst motivation and learning result  by Using Video Based Learning in English . The Methodology of This research is quantitative research, namely by conducting classroom action research, where in looking at the results of this research a test is given to the control group and experimental group by giving a pre-test and post-test. The population of this study was Singosari Class X High School, and the sample consisted of 62 people. The results of this research were the experimental class sa pre-test 51.48 and post test 79.25. while in the control group class it was 47.29 and post test 54.87. This figure is proof of the effectiveness of Video Based Learning users in improving the English grammar skills of class X Singosari Delitua High School students. REFERENCES Adriyani, N.L. & Suniasih. W.(2021) Developmen of Learning Video Based Learning on Problem Solving Characteristic of Anials and Their Habitats Cintain in Science Subject on 6th grade.Jurnal of Education 5(1) 7-47                                                        Agustini, Ketut dan Jero GedeNgarti (2020). Pengembangan Video Pembelajaran Untuk Meningkatkan Motivasi Belajar Siswa Menggunakan Modal R&D. Jurnal Ilmiah  Pendidikan (JIIP), 4(1) DOI:http://dx.doi.org/10.23887//jipp.v41I.18403 Ary, Donald. 2005. Introduction to Research in Education. New York: Northern Illionis   University Cut Dhien, Nurwahidah, Zahara Zahara, Ibnu Sina. (2021). Media Video Pembelajaran Dalam Meningkatkan Motivasi dan Prestasi Mahasiswa.Vol 17 No.1   Fitria, Eka. (2021) .Analisis Pemanfaatan Meia Online pada Pembelajaran Daring Fisika Terhadap Motivasi Belajar Siswa. Jurnal of Innovation in Teaching and Instructional Media.6(7) 56-60 Lupita, L., & Amdriani, S. (2021). Video Edukatif Youtube Berbantuan Powtoon Aplication Berbasis etnomatematika Materi Bangun Ruang Sisi Lengkung Siswa SMP/MTs. Maju : Jurnal Ilmiah Pendidikan Matenatika, 8(1),11. Heo, M., Toomey, N. (2020). Learning With Multimedia: The Effect Of Gender, Type of Multimedia Learning resources, and spatial ability. Computer and Education, 146, 103747. https://doi.org/10.1016/j.compedu.2019.103747 Luritawaty, I. P. (2018) Pembelajaran take and Give dalam upaya mengembangkan kemampuan Pemahaman Konsep Matematis. Mosharafa : Jurnal Pendidikan Matematika, 7(2), 179-188. Lelis Adrianty at al(2024). Meningkatkan Motivasi Belajar dengan Penggunaan Vidio Pembelajaran di MtsS Asy-Syarif Sidang Koto Laweh. Jurnal Ilmu Sosial, Pendidikan Dan Humaniora Vol. 3, No.1 April 2024. e-ISSN: 2829-3886; p-ISSN: 2829-3479, Hal. 244-251 DOI: https://doi.org/10.56910/jispendiora.v3i1.1250  Novita, L., Sukmanasa, E.m & Pratama, M.Y. (2019). Penggunaan Media Pembelajaran Video Terhadap Hasil Belajar Siswa SD. Indonesia Jurnal of Primary Education Penggunaan, 3(2), 62 Pradilasari, L., Gani, A., &Khaldun(2019) . Pengembangan Media Pembelajaran Berbasis Audio Visual  Pada MAteri Koloid Untuk Meningkatkan Motivasi dan Hasil Belajar Siswa SMA. Jurnal Pendidikan Sains Indonesia, 7(1), 9-15 Putri marliani, Lita. (2021). PengembanganVidioPembelajaranUntukMeningkatkan MotivasiBelajarSiswaSekolahDasar. UIN Syarif Hidayatullah. Sadewo, Y. D., & Purnasari, P.D. (2021). Pengembangan Vidio Pembelajaran Matematika Berorientasi Kebudayaan Lokal Pada Sekolah Dasar. Sebatik, 25(2), 590-597 Sari, Wan Nuridiana. (2021). Pendidikan Karakter Melalui Pembelajaran IPS. Jurnal Inovasi Penelitian. Vol 1 No. 1 Hal 2255-2262. Suryana, D., & Hijriyani, A. (2021). Pengembangan Media Video Pembelajaran Tematik Anak Usia Dini 5-6 Tahun Berbasis Kearifan Lokal. Jurnal Pendidikan Anak Usia Dini, 6(2), 1077-1094. https://doi.org/10.31004/obsesi.v6i2.1413 Soucy, J.N., Owens, V. A. M., Hadjistavropoulos, H.D., Dirkse, D. A., & Dear, B. F. (2016). Educating Patiens about internet- delivered cognitive behavior therapy: Perception among treatment seekers and non-treatment seekers before and after viewing and educational video. Internet interventions, 6, 57-63. Syaparuddin. (2020). Strategi Pembelaaran Aktif Dalam Meningkatkan Motivasi Belajar Peserta Didik. Jurnal Pendidikan Guru Sekolah Dasar. 25(4) 256-280. Tegeh, Simamora, & Dwipayana. (2019). Pengembangan Media Video Pembelajaran  Dengan Model Pengembangan 4D Pada Mata Pelajaran Agama Hindu.Jurnal Mimbar Imu , 24(2), 158-166.https://doi.org/10.22219/jpg.vIiI.12462 Taqiya, Nuroso & Reffiane.(2019) Pengaruh Model Pembelajaran Terpadu Tipe Connectea Bantu  Media Video Animasi. Mimbar PGSD Undiksha, 7(3), 289-295 Tegeh, Simamora, & Dwipayana. (2019). Pengembangan Media Video Pembelajaran Dengan Model Pengembangan 4D Pada Mata Pelajaran Agama Hindu. 7(5). 242-245 Yunita, dkk.(2019). Pengembangan Video Pembelajaran Matematika melalui Moel Pembelajaran Flipped Classroom di Sekolah Menengah Kejuruan, Imajiner.v i6,4868. Yusnia, Y.(2019). Penggunaan Media Video dalam Pembelajaran Literasi Sains Untuk Mahasiswa PGAPAUD. Cakrawala Dini: Jurnal Pendidikan Usia Dini, 10(1), 71-75,https://doi.org/10.17509/cd.vl0iI. 17436